Kualitas Audit dan Mitigasi Bias Kognitif Investor: Tinjauan Sistematis Berbasis Teori Sinyal dan Keagenan - Bagus Samudro Aji Luhur (Al-Buhuts, 2026)
The efficient market hypothesis assumes that investors process available information rationally when forming investment decisions. Behavioral finance research accumulated over the past two decades challenges this assumption, showing that decisions are routinely distorted by overconfidence, herding, and cognitive dissonance. Audit quality has been proposed as an external governance mechanism capable of narrowing this gap between assumed rationality and actual investor behavior, yet the specific pathways linking audit attributes to particular biases remain scattered across the auditing and behavioral finance literatures rather than examined together.This study synthesizes how audit quality mitigates investor cognitive bias by integrating Signaling Theory, Agency Theory, and Behavioral Finance, and maps which audit attributes (auditor reputation, audit fee, industry specialization, audit tenure, and Key Audit Matters transparency) correspond to which bias-reduction mechanism.A Systematic Literature Review, adapted from the staged selection logic of the PRISMA 2020 protocol (Page et al., 2021), was conducted across Scopus, Web of Science, Emerald Insight, ScienceDirect, and SINTA-indexed journals, covering publications from 2015 to 2025. Search terms combined “Audit Quality,” “Cognitive Bias,” “Behavioral Finance,” “Herding Behavior,” “Overconfidence,” and “Key Audit Matters,” applied iteratively together with citation snowballing rather than as a single formal database export; consequently, initial record counts are not reported as a single quantitative figure. After eligibility screening was applied consistently throughout this iterative process, 33 studies were retained for thematic synthesis.The synthesis indicates that audit quality is associated with lower herding behavior, weaker managerial-to-investor transmission of overconfidence, and reduced cognitive dissonance, primarily through three mechanisms: (1) higher information precision that lowers investors’ reliance on social signals, (2) auditor monitoring that constrains overly optimistic management projections before they reach the market, and (3) KAM disclosure that confronts investors with verified risk information. These patterns are more consistent for information-precision and monitoring mechanisms than for the audit fee–quality relationship, where findings across the reviewed studies are mixed.The study repositions audit quality as a behavioral governance mechanism rather than a purely compliance-oriented function, and offers an integrated conceptual framework linking specific audit attributes to specific investor biases. This framework can inform how regulators design KAM disclosure requirements and how retail investors evaluate audit signals, while also outlining where the evidence base still requires primary empirical testing.